Tinjauan Kapasitas Persediaan Produk Fuji Seat PT. Tri Jaya Teknik Karawang - Adiyanto, Aries; Herwanto, Dene (Jurnal Media Teknik dan Sistem Industri, 2021)
PT. Tri Jaya Teknik Karawang is an engineering company engaged in fabrication, machining and side parts. PT. Tri Jaya Teknik started pioneering a business since 2007 and started owning and occupying its own workshop in 2009. Currently the company already has 2 plant workshops with a total area of 3,080 m2 and has about 100 employees. One of the products produced is Fuji seat, based on the data collected there are 3 parts of the process. The 3 parts of the process are repair 1, repair 2, repair 3. With each there is a check parts & packing table. The method used in companies to manage raw material inventories is still conventional, namely by making continuous purchases without estimating according to needs. So that there is often an excess of raw materials or a shortage of raw materials at a certain time, this makes the costs incurred inefficient and often disrupts the production process. A review of the inventory capacity of Fuji Seat products in this study was carried out using the Economic Order Quantity (EOQ) model. The main raw material inventory data used is Fuji Seat in the 2016-2019 period. Holding cost raw materials is set by PT. Tri Jaya Teknik Karawang is 2.5% of the price per pcs, this value is used for procurement and repair of tools and equipment in the warehouse. If there is no damage, the cost is allocated to the warehouse manager in that month. Meanwhile, the cost of ordering which consists of the price of goods and shipping costs is determined by PT. Tri Jaya Teknik Karawang, amounting to IDR 100,000.00. This fee includes administration and transportation costs. Administrative costs, namely executive salaries and other supporters, as well as taxes related to the company. The cost of shipping transport is the distance traveled and the weight of the product ordered. Based on the calculation of EOQ (Economic Order Quantity), the most economical amount of raw materials using the EOQ model is 6,815.5 Pcs with 187 purchases a year.Â PT. Tri Jaya Teknik Karawang adalah perusahaan engineering yang bergerak di bidang fabrikasi, machining dan part samping. PT. Tri Jaya Teknik mulai merintis bisnis sejak tahun 2007 dan mulai memiliki dan menempati workshop sendiri di tahun 2009. Saat ini perusahaan telah memiliki 2 plant workshop dengan total luas 3.080 m2 dan memiliki karyawan berjumlah sekitar 100 orang. Salah satu produk yang dihasilkan adalah fuji seat, berdasarkan data yang dikumpulkan ada 3 bagian proses. 3 bagian proses itu adalah repair 1, repair 2, repair 3. Dengan masing-masing terdapat meja check part & packing. Metode yang digunakan pada perusahaan untuk mengelola persediaan bahan baku masih secara konvensional, yaitu dengan melakukan pembelian terus menerus tanpa memperkirakan sesuai dengan kebutuhan. Sehingga seringkali terjadi kelebihan bahan baku atau kekurangan bahan baku di saat tertentu, hal ini membuat biaya yang dikeluarkan menjadi tidak efisien dan sering kali mengganggu proses produksi. Tujuan penelitian ini yaitu mampu mengetahui perhitungan EOQ dan frekuensi pembelian yang paling ekonomis dalam perusahaan. Tinjauan kapasitas persediaan produk Fuji Seat dalam penelitian ini dilakukan dengan menggunakan model Economic Order Quantity (EOQ). Data persediaan bahan baku utama yang digunakan adalah Fuji Seat pada periode 2016-2019.Biaya penyimpanan bahan baku di tetapkan oleh pihak PT. Tri Jaya Teknik Karawang sebesar 2,5% dari harga per pcs, nilai tersebut digunakan untuk keperluan pengadaan dan perbaikanÂ